The iron cage revisited: institutional isomorphism and collective rationality in organizational fields - DiMaggio, Paul Joseph (2005)
What makes organizations so similar? We contend that the engine of rationalization and bureaucratization has moved from the competitive marketplace to the state and the professions. Once a set of organization emerges as a field, a paradox arises: rational actors make their organizations increasingly similar as they try to change them. We describe three isomorphic processes - coercive, mimetic, and normative - leading to this outcome. We then specify hypotheses about the impact of resource centralization and structuration on isomorphic change. Finally, we suggest implications for theories of organizations and social change.